Reprogramming Immune Cells for Enhanced Cancer Immunotherapy: Targets and Strategies - Dong, Yan; Wan, Zhuo; Gao, Xiaotong; Yang, Guodong; Liu, Li (Frontiers in Immunology, 2021)
Cancer is one of the leading causes of death and a major public health problem all over the world. Immunotherapy is becoming a revolutionary clinical management for various cancer types. Restoration of aberrant immune surveillance on cancers has achieved markable progress in the past years by either in vivo or ex vivo engineering of the immune cells. Here, we summarized the central roles of immune cells in tumor progression and regression, and the existing and emerging strategies for different immune cell-based immunotherapies. In addition, the current challenges and the potential solutions in translating the immunotherapies into the clinic are also discussed.